SUGAR MAPLE (ACER SACCHARUM MARSHALL) IN THE CONDITIONS OF THE KHARKIV REGION - Tereshchenko, L. I.; Los, S. A.; Grachova, M. A.; Ryzhenko, T. S. (Forestry and Forest Melioration, 2018)
Introduction The natural range of sugar maple (Acer saccharum Marshall) is the eastern part of North America (Canada, USA). It is one of the highest species of maple which can grow up to 40 m. The sugar maple is a valuable species due to the high quality of its wood, its ability to produce maple juice and a high decorative value. Due to its sensitivity to ground compaction, heat, drought and road salt, sugar maple is not widely used in urban street plantings, but it is still recommended for parks and other areas away from roads where the soil is loose and well-drained (Gilman & Watson 1993). In Ukraine, sugar maple was first introduced in 1929 in the Nikitsky Botanical Garden and after that – in other dendrological parks. Its certain representatives are available in the Ustymivsky Dendropark (Poltava Region), as well as in Kyiv, Zhytomyr, Lviv, Uzhhorod and Vinnytsia (Kolesnykov 1974, Oleksiychenko & Manko 2012, Bilyk 2012, Peshyk & Astakhova 2017, Kavun & Gnatyuk 2017). Currently, there are only data on the area where sugar maple grows, but there is a significant gap in the data concerning its growth and development. The sugar maple which is in the Ustymivsky Dendrology Park is classified as a species highly adaptable to the conditions it grows in and of excellent ornamental value (Bilyk 2012). The data obtained by Russian and Bilorusian researchers indicate a sufficient resilience of sugar maple trees in the city conditions within Orel (Kyseleva et al. 2016), Volgograd (Burul & Chumachenko 2015) and Gomel (Padutov et al. 2013). The aim of the study was to determine how suitable the sugar maple is for plantations of different purposes within Kharkiv Region based on the complex assessment of the growth and development of the species in the experimental plantation. Materials and Methods The seeds of the sugar maple were conveyed to Ukrainian Research Institute of Forestry and Forest Melioration in 1985 by the Ministry of Forestry of Ukraine, which were delivered there by an employee of the Embassy of Ukraine in the United States. The samples had labels: "wild north", "wild south", "plantation of the north" and "plantation of the south". The experimental plantation was established in 1987 in the Pivdenne Forestry of the State Enterprise "Kharkiv Forest Research Station" of URIFFM, in conditions of fresh maple-lime fertile oak forest type. There are 7 variants on the plot, 2 of which were defined as "With no number 1" and "With no number 2", one variant as "North, a mix"(seeds of a natural and man-made origin). The Sugar maple experimental plantation was first studied in 1989. In autumn 2018, at the age of 33, it was examined for the second time. We defined a diameter of the stem, height, selection category, state, presence of defects and damage for each tree as well as calculated the average figures for all variants. In addition, we determined mensuration indexes according to the generally accepted methods; the selection category and the status category – according to the UkrURIFFM Classification (Volosyanchuk 2003). Each index was evaluated by a 5-grade scale. We estimated variants in terms of the average height and diameter, the proportion of trees of the 1st and 2nd selection categories, the average category of the state and the presence of reproduction (Grybovich et al. 2018). Due to the fact that there was no control variant on the plot, the growth rates were compared with the data in the yield tables given for the planted fully stocked English oak stands of the same age (Shvidenko et al. 1987) and with an average value per plot. To determine the success level for the introduction of sugar maple, we applied the complex evaluation scale (Grybovich et al 2018) with refinements. Results The results of the research done in 1989 (biological age of 4 years) showed that the variants of southern origin significantly exceeded the northern-origin variants in height and were characterized by a better state and quality. According to the research done in 2018 (biological age of trees was 33 years), the plant preservation in variants was 23.2%. The variants of a man-made origin had somewhat higher mortality. The trees at the plot had the diameter of 3 to 35 cm and the height of 11.0 to 25.6 m. The average values of the diameter of the variants ranged from 15.8 to 17.7 cm, and the height - from 18.2 to 21.1 m. In diameter, the sugar maple variants lagged behind the tabular data for English oak (21.5–29.8%). In height, two variants (“With no number 1” and “With no number 2”) exceeded the oak by 4.5–5.9% and five variants fell behind by 0.03 - 8.5%. Variants from the north grew slower (18.5 ± 0.54 m) than from the south (19.9 ± 0.39 m). There are no plus trees. The share of the best normal trees is from 0 ("South, natural origin") to 18.2% ("North, natural origin"). The trees of a satisfactory state prevailed in quantity. At that, almost half of them had dry branches in the upper part of the crown. Furthermore, the crooked stems, double trunks or lateral shoots dominated among the defects of stems. The trees in a satisfactory and good state prevailed on the plantation. They made 70% of all the trees. All the variants on the experimental plantation had fruits. Conclusions The main factors that weaken the development of Acer saccharum in conditions of the introduction are a lack of moisture and both early autumn and late spring frost. The main decline of plants occurred during the first three years after planting. The tendency to the best growth in height among the trees of southern origin was seen as early as at the age of 4 years. No significant difference in height between the variants was found. Based on the results of the comprehensive assessment, the variants scored from 11.5 to 14.5 points out of 20 possible. 6 out of 7 variants were including into the second group of perceptiveness. Sugar maple is recommended to introduce in plantings that will perform recreational and health and protective functions in conditions of moderate anthropogenic loading, as well as to use to green non-industrial city zones. Key words: Acer saccharum, experimental plantation, viability, growth, selection category, state, reproduction, complex assessment.